2021
DOI: 10.1038/s41598-021-86164-8
|View full text |Cite
|
Sign up to set email alerts
|

In situ recordings of large gelatinous spheres from NE Atlantic, and the first genetic confirmation of egg mass of Illex coindetii (Vérany, 1839) (Cephalopoda, Mollusca)

Abstract: In total, 90 gelatinous spheres, averaging one meter in diameter, have been recorded from ~ 1985 to 2019 from the NE Atlantic Ocean, including the Mediterranean Sea, using citizen science. More than 50% had a dark streak through center. They were recorded from the surface to ~ 60–70 m depth, mainly neutrally buoyant, in temperatures between 8 and 24°C. Lack of tissue samples has until now, prohibited confirmation of species. However, in 2019 scuba divers secured four tissue samples from the Norwegian coast. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…In winter, most I. coindetii were immature or maturing, while in summer almost exclusively larger individuals were fished; mostly mature and spent . Furthermore, mated females with spermatangia bundles, were observed in summer and Illex eggs were identified in the Greater North Sea and adjacent waters (Barrett et al 2021;Ringvold et al 2021). Consequently, it is very likely that the species started to reproduce in the area with a hatching period at least from June to December Barrett et al 2021).…”
Section: Illex Coindetiimentioning
confidence: 99%
“…In winter, most I. coindetii were immature or maturing, while in summer almost exclusively larger individuals were fished; mostly mature and spent . Furthermore, mated females with spermatangia bundles, were observed in summer and Illex eggs were identified in the Greater North Sea and adjacent waters (Barrett et al 2021;Ringvold et al 2021). Consequently, it is very likely that the species started to reproduce in the area with a hatching period at least from June to December Barrett et al 2021).…”
Section: Illex Coindetiimentioning
confidence: 99%
“…The current reproductive success in the North Sea (first observed in 2016) probably results from rising temperatures and prevailing currents (Barrett et al., 2021; Oesterwind et al., 2022) and has led to an independent stock. The North Sea appears to be the northernmost breeding area, with main spawning grounds in the Central and Northern North Sea (Barrett et al., 2021), while floating egg masses have been observed in the Norwegian Channel (Ringvold et al., 2021). The bathymetry and hydrology of the North Sea, as a shelf sea with an average depth of 90 m and a relatively narrow connection to the Atlantic Ocean (ESaTDOR, 2013), could prevent emigration from this area by passive drifting egg spheres and hatchlings of I. coindetii .…”
Section: Discussionmentioning
confidence: 99%
“…Mean statolith shapes of Illex coindetii and Loligo forbesii (all maturity stages and sexes) from the Balearic Sea (blue), Celtic Sea (grey), North Sea (Q1 & Q3 combined; black), Sea East of Sardinia (red), Sea West of Sardinia (orange), Sea West of Scotland (green), South Adriatic Sea (yellow), Western Ionian Sea (purple) of the North East Atlantic and Northern Mediterranean Sea during 2021-2022. Intersection of coordinate lines corresponds to the statolith centroid.North Sea appears to be the northernmost breeding area, with main spawning grounds in the Central and Northern North Sea(Barrett et al, 2021), while floating egg masses have been observed in the Norwegian Channel(Ringvold et al, 2021). The bathymetry and hydrology of the North Sea, as a shelf sea with an average depth of 90 m and a relatively narrow connection to the Atlantic Ocean(ESaTDOR, 2013), could prevent emigration from this area by passive drifting egg spheres and hatchlings of I. coindetii.…”
mentioning
confidence: 99%
“…O desenvolvimento embrionário em laboratório dura entre 10 e 14 dias a 15°C; este valor provavelmente reflete o período sob condições naturais condições (Sanchez et al, 1998). Recentemente massas de ovos deste formato de esferas foram observadas na costa Noroeste da Noruega em aproximadamente 40 m de profundidade, e a análise genética confirmou que os ovos eram de I. coindetii (Ringvold et al, 2021).…”
Section: Características Genéticasunclassified

Ficha de Illex coindetii

Tatiana Leite,
Catarina Cardoso de Melo,
João Bráullio de Luna Sales
et al. 2024
Datasets - Sistema SALVE - ICMBio